Analysis of the burden and trend of injury in Sichuan, China, from 2006 to 2015: results from the national injury surveillance system - Xianping Wu; Xiaofang Chen; Peng Cai; Zhihao Liu; Ying Deng; Guanghui Yi; Jiang Xu; Shirong Huang; Rongsheng Luan (BMJ Open)
Objective This study investigates the distribution, burden and trends of injuries in Sichuan, China.Design A surveillance study using injury data collected by the National Injury Surveillance System.Setting and participants 312 511 injury cases reported in the National Injury Surveillance System in Sichuan, China, from 2006 to 2015.Primary outcome measures Years of potential life lost (YPLL) were calculated to determine the disease burden from injuries. Trend analysis was performed to assess the trends in specific injuries over time.Results A total of 312 511 injury cases were reported in the last 10 years in Sichuan with 192 904 (men: 58.58%) and 119 607 (men: 67.11%) cases from the urban and rural surveillance hospitals, respectively. The annual number of injury cases increased from 21 257 in 2006 to 44 112 in 2015 with an average annual increase of 8.45%. The top three common causes of injury were fall (29.3%), animal-related injury (19.1%) and road-related injury (14.6%) in the urban area and fall (38.4%), road-related injury (17.2%) and blunt injuries (16.0%) in the rural area. YPLLs from injuries accounted for 13% of the total YPLLs in the urban area.Conclusions The number of injury cases varied according to rural/urban areas and gender and increased sharply in Sichuan over the last decade. It is necessary to develop targeted prevention and control measures to reduce the disease burden of injuries.